Benchmarking Accomplishments of Leaders in American Surgery and Justification for Enhancing Diversity and Inclusion. Issue 6 (December 2020) - Butler, Paris D.; Pugh, Carla M.; Meer, Elana; Lett, Lanair A.; Tilahun, Estifanos D.; Sanfey, Hilary A.; Berry, Cherisse; Stain, Steven C.; DeMatteo, Ronald P.; Vickers, Selwyn M.; Britt, L. D.; Martin, Colin A.
Abstract : Objective: To comprehensively assess the level of achievement and demographics of national surgical society presidents. Background: Data on the accomplishments needed to rise to positions of national surgical leadership is scarce and merit alone does not always yield such opportunities. Recognizing the shortcomings of sex and ethnic diversity within academic surgical leadership, the American College of Surgeon (ACS), American Surgical Association (ASA), Association of Women Surgeons (AWS), and the Society of Black Academic Surgeons (SBAS) partnered to address these challenges by performing a comprehensive assessment of their presidents over the last 16 years. Methods: ACS, ASA, AWS, and SBAS presidents' CVs, at the time of their presidential term, were assessed for demographics and scholastic achievements. Regression analyses controlling for age were performed to determine relative differences across societies. Results: A total of 62 of the 64 presidents' CVs were received and assessed (97% response rate). There was a large discrepancy in the average age in years of ACS (70) and ASA (66) presidents compared to the AWS (51) and SBAS (53) presidents. For the ACS and ASA cohort, 87% were male and 83% were White, collectively. After controlling for age (52), the AWS and SBAS presidents' scholastic achievements were comparable to the ACS (and ASA) cohort in 9 and 12 of the 15 accessed metrics, respectively. Conclusion: The ACS and ASA presidents' CVs displayed unsurpassed scholastic achievement, and although not equivalent, both the AWS and the SBAS presidents had comparable attainment. These findings further substantiate that women and ethnic minority surgeons are deserving of additional national leadership consideration as organized medicine pursues a more diverse and reflective physician workforce.